2020
DOI: 10.3928/23258160-20200804-06
|View full text |Cite
|
Sign up to set email alerts
|

Reading Speed as an Objective Measure of Improvement Following Vitrectomy for Symptomatic Vitreous Opacities

Abstract: Background and Objective: There is currently no objective measure of the visual deficits experienced by patients with symptomatic vitreous opacities (SVO) that would also correlate with the functional improvement they report following vitrectomy. This study aims to determine whether reading speed can be used as a reliable outcome measure to assess objectively the impact of both SVO and vitrectomy on patients' visual performance. Study Design/Materials and Methods: 20 adult patients seeking surgery for SVO were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Ryan et al recorded scanning laser ophthalmoscopy (SLO) images of vitreous in static and dynamic fashion, and the findings were graded by masked observers (Supplemental Digital Content http://links.lww.com/COOP/A40 – Ryan SDC2 – SLO video demonstrating symptomatic vitreous opacities http://links.lww.com/COOP/A41). All patients had marked improvement in SLO appearance, but the severity grade of opacities did not correlate to VFQ-25 score improvement [10 ▪ ].…”
Section: Assessment Of Preoperative Dysfunction and Surgical Benefitmentioning
confidence: 77%
See 2 more Smart Citations
“…Ryan et al recorded scanning laser ophthalmoscopy (SLO) images of vitreous in static and dynamic fashion, and the findings were graded by masked observers (Supplemental Digital Content http://links.lww.com/COOP/A40 – Ryan SDC2 – SLO video demonstrating symptomatic vitreous opacities http://links.lww.com/COOP/A41). All patients had marked improvement in SLO appearance, but the severity grade of opacities did not correlate to VFQ-25 score improvement [10 ▪ ].…”
Section: Assessment Of Preoperative Dysfunction and Surgical Benefitmentioning
confidence: 77%
“…There was an improvement postoperatively of 19.3% in the composite score, 28.13% in general vision, and 27.37% in near activities. Ryan et al used the VFQ-25 and found an average score change of 17.8 points overall, and 21.1 points in near activities subscores [10 ▪ ]. Schultz-Key used a modified 12-question survey, and found that 88% of patients were satisfied with the results of the operation, and 73% felt that their vision was either better or much better following surgery [2].…”
Section: Assessment Of Preoperative Dysfunction and Surgical Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a survey conducted on patients with floaters showed that they were willing to trade off an average of 1.1 years out of every 10 years of their remaining life to get rid of the symptoms associated with floaters, and were also willing to take a 7% risk of blindness and 11% of death to get rid of symptoms associated with floaters [ 18 ]. Additionally, several studies have reported significant improvement in symptoms [ 16 ], patient satisfaction [ 17 ], quality of life [ 19 , 20 ] and reading speed [ 20 ] after vitrectomy for the removal of vitreous floaters.…”
Section: Discussionmentioning
confidence: 99%